Hubungan Topografi Wilayah Tempa Tinggal Ibu Menyusui dengan Kadar Fe dalam ASI di Sumatera Barat - Yonaniko Dephinto; Dewi susilawati (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2020)
The quantity and quality of breast milk produced are affected by the food consumed by mothers daily. Judging from the geographical condition and aquatic resources, people in lowland (coastal) blood will consume more animal foods that come from the sea, such as fish, shellfish, and the like. People in the highlands will be more likely to consume food items derived from small livestock such as poultry and the like. This is thought to have an impact on the levels of Fe in breast milk (ASI), considering that the concentration in breast milk is influenced by the mother's diet. This study is an observational study with a cross-sectional comparative design to see the differences in Fe levels in breast milk in breastfeeding mothers who live in the highlands and the lowlands. The sample used is the minimum sample for experimental research and questionnaires, namely 40 respondents for each region. To determine Fe levels, measurements were taken in the LLDIKTI X integrated laboratory using AAS. The FFQ questionnaire was used to determine the nutritional content. Data analysis used the Mann-Whitney nonparametric test. The results of this study were that the iron intake in breastfeeding mothers was higher in the lowlands than mothers in the highlands so that there was a regional topographic relationship to iron levels in breastfeeding mothers with a p-value: 0.000.